TUMBUHAN OBAT KHUSUS KESEHATAN REPRODUKSI WANITA DI DUSUN KAYU BAONG DESA PEKAWAI KECAMATAN SAYAN KABUPATEN MELAWI - Ratnasari, Desi; Kartikawati, S M; Muflihati, . (JURNAL HUTAN LESTARI, 2017)
The society of Kayu Baong Hamlet utilizes a special plantation of reproductive health as a traditional medicine that has been used inherited. The purpose for knowing the cultivation of the pharmacy and the exploiting, the treatment for the health of reproductive health. This research is descriptive, using the snowboll samplingÂ  technique which is one of the most commonly used methods performed in chains by requesting information on the sample people. The data of the research result are covering genes of plants, health benefits, parts used, processing, directions in use. The results obtained in the field of plant genes used by the community of Kayu Baong Village Pekawai Village, Sayan Sub-district of Melawi Regency, obtained 23 species of medicinal fish from 21 family and if in groups based on habitat in face herbal most widely utilize asobat, based on the parts that are used by many people who usetheit of 10 species (47,82) and from the way of processing was the way boiled more widely used that is as much as 10 spesies (43.47%) based on its use, it turns out by way of drinking more that is 13 spesies (56.53%), and from the way the use of drugs was to treat bleeding after childbirth and at least. Keywords: Ethnobotany, Plant medicines, reproductive ladies.